TV programmimg priorities - Draganov, Ivan (Yearbook Telecommunications, 2016)
Purpose: We analyze the development of the television field after the liberalization and licensing procedures in Bulgaria. Results: We outline the programming priorities and the features of the main TV channels. Contributions: We summarize what the Bulgarian TV audience has won after the liberalization of the TV area in the country.